2010
DOI: 10.2147/ijn.s9962
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable polymer based tamoxifen citrate loaded nanoparticles and effect of some manufacturing process parameters on them: a physicochemical and in-vitro evaluation

Abstract: Abstract:The aim of the present study was to develop nanoparticles of tamoxifen citrate, a non-steroidal antiestrogenic drug used for the treatment of breast cancer. Biodegradable poly (D, L-lactide-co-glycolide)-85:15 (PLGA) was used to develop nanoparticles of tamoxifen citrate by multiple emulsification (w/o/w) and solvent evaporation technique. Drug-polymer ratio, polyvinyl alcohol concentrations, and homogenizing speeds were varied at different stages of preparation to optimize the desired size and releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…FTIR was conducted to determine possible interaction (if any) between the drug and the excipients. For ML-based formulation, pure drug (AZT), CHO, ML, BHT, physical mixture (PM) of CHO, ML, BHT, physical mixture (PMD) of CHO, ML, BHT and drug AZT, lyophilized formulation without drug (MGB) and lyophilized formulation with drug (MGF) and for SL-based formulation, AZT, CHO, SL, BHT, physical mixture (PM-1) of CHO, SL, BHT, physical mixture (PMD-1) of CHO, SL, BHT and AZT, lyophilized formulation without drug (SYB) and lyophilized formulation with drug (SYF) were scanned at 4000–400 cm −1 using FTIR instrument (JASCO International Co. Ltd., FTIR 4200, Tokyo, Japan) using their pellets formed by mixing with potassium bromide (KBr) at 1:100 ratio and compressing with a hydraulic press (Sahana et al., 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FTIR was conducted to determine possible interaction (if any) between the drug and the excipients. For ML-based formulation, pure drug (AZT), CHO, ML, BHT, physical mixture (PM) of CHO, ML, BHT, physical mixture (PMD) of CHO, ML, BHT and drug AZT, lyophilized formulation without drug (MGB) and lyophilized formulation with drug (MGF) and for SL-based formulation, AZT, CHO, SL, BHT, physical mixture (PM-1) of CHO, SL, BHT, physical mixture (PMD-1) of CHO, SL, BHT and AZT, lyophilized formulation without drug (SYB) and lyophilized formulation with drug (SYF) were scanned at 4000–400 cm −1 using FTIR instrument (JASCO International Co. Ltd., FTIR 4200, Tokyo, Japan) using their pellets formed by mixing with potassium bromide (KBr) at 1:100 ratio and compressing with a hydraulic press (Sahana et al., 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the yield of NLs from the utilized total amount of raw materials of NLs preparation, lyophilized dried NLs of each batch were weighed and the percentage of yield was calculated by using the following equation as mentioned earlier (Sahana et al., 2010 ). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many studies have been performed and showed spherical shaped nanoparticles [22, 26, 32, 33]. Field emission SEM (FE-SEM) is more sensitive than SEM as it allows detecting samples within nanometer range [34].…”
Section: Detailed In Vitro Physicochemical Characterizationsmentioning
confidence: 99%
“…Tamoxifen citrate (TAM) is commonly employed as a non-steroidal estrogen antagonist in ER+ breast cancer therapeutics, in addition to long-term preventive use in risky and post-menopausal women [ 19 ]. TAM acts by causing apoptosis through cell-cycle arrest [ 20 ]; it also acts as an anti-oxidant [ 21 ] and may stimulate tumoricidal effects on ER-cells through increased inhibitory growth factor production [ 22 ]. Although promising, TAM is eliminated via hepatic first-pass metabolism with a detectable drug concentration up to 24 h of oral administration [ 23 ].…”
Section: Introductionmentioning
confidence: 99%